Description of Kumatoeides gen. nov. (Coleoptera: Chrysomelidae, Eumolpinae) from New Caledonia - Gómez-Zurita, Jesús (Zootaxa, 2018)
In this article, I describe a new endemic genus of New Caledonian Eumolpinae, Kumatoeides gen. nov. (tribe Eumolpini), and eight new species currently conforming the genus: K. anomala sp. nov., K. aulacia sp. nov. (generic type), K. leptalei sp. nov., K. megale sp. nov., K. metallica sp. nov., K. millei sp. nov., K. tarsalis sp. nov. and K. wanati sp. nov. Some easily recognizable defining traits of this new genus of fairly small species (2.23–3.20 mm) are the glabrous dorsum, aligned punctures on elytra in eight regular striae plus short scutellar and a subhumeral striae, convex elytral intervals, and the enlarged and elongate first pro- and mesotarsomeres of males. One species originally described in the genus Montrouzierella Jolivet, Verma et Mille is transferred to the new genus as Kumatoeides costata (Jolivet, Verma et Mille) nov. comb. A preliminary phylogenetic analysis using partial cox1 and rrnS mtDNA sequences of five species of Kumatoeides gen. nov. together with a representative sample of species of Eumolpinae from New Caledonia supports the monophyly of the genus and the existence of two main groups as recognized based on morphological traits. However, data are not conclusive about the relationship of the new genus with other New Caledonian lineages, although suggest a closest relationship with some unidentified species most similar to some representatives of the genus Samuelsonia Jolivet, Verma et Mille but with morphological similarities with Kumatoeides gen. nov., including dilated male protarsomeres, similar antennomere proportions and tendency to aligned rows of punctures on elytra, at least apically.